The underground church - Bach, Eugene, 1976- (New Kensington, PA : Whitaker House, 2014)
"An inside look at the history, sufferings, explosive growth, and missionary focus of the underground church movement in China, with personal interviews and an assessment of the future of the movement"--
Keywords: China; Church history -- 20th century; China -- Church history -- 21st century